Hubungan Pola Asuh Ibu Dengan Kejadian Stunting Pada Balita Usia 24-59 Bulan - Nursiah, Andi; Rahmat, Rezqiqah Aulia (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Stunting remains a public health problem in Indonesia. Data from the 2024 Indonesian Nutritional Status Survey (SSGI) shows that the prevalence of stunting decreased from 21.5% (2023) to 19.8% (2024), but the number of stunted children under five remains around 4.48 million. Maternal parenting patterns, including feeding, stimulation, and health care, play a crucial role in preventing stunting. Objective: This study aims to analyze the relationship between maternal parenting patterns and the incidence of stunting in toddlers aged 24–59 months. Methods: The study used an observational analytical design with a cross-sectional approach. The study population was mothers of toddlers aged 24–59 months. The sample was selected using proportional random sampling with a total of 30 respondents (adjusted to the research results). The instruments used were a parenting questionnaire and measurement of toddler nutritional status using the TB/U index (height for age) based on WHO standards. Data analysis was performed using the Chi-Square test with a 95% significance level (p < 0.05). Results: The study showed that most mothers with good parenting practices had toddlers with normal nutritional status, while mothers with poor parenting practices were more likely to have toddlers with stunting. Statistical tests showed a significant relationship between maternal parenting practices and the incidence of stunting in toddlers aged 24–59 months (p < 0.05). Conclusion: Maternal parenting practices are associated with the incidence of stunting in toddlers aged 24–59 months. Interventions based on parenting education, increasing maternal knowledge, and strengthening the roles of families and health workers are essential to reduce stunting rates in Indonesia.